2021
DOI: 10.1364/boe.411620
|View full text |Cite
|
Sign up to set email alerts
|

Widely-tunable synchronisation-free picosecond laser source for multimodal CARS, SHG, and two-photon microscopy

Abstract: We demonstrate a continuous wave (CW) seeded synchronization-free optical parametric amplifier (OPA) pumped by a picosecond, 1 µm laser and show its performance when used as a simple yet powerful source for label-free coherent anti-Stokes Raman scattering (CARS), concurrent second harmonic generation (SHG), and two-photon fluorescence microscopy in an epi-detection geometry. The average power level of above 175 mW, spectral resolution of 8 cm −1 , and 2 ps pulse duration are well optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Frequency-doubled picosecond pulses will then pump two travelingwave optical parametric amplifiers (OPAs), one of them generating the Raman pump for the SRS. This way, the system will be made synchronization-free and simpler than typical Raman setups [15]. The other OPA, seeded by the fundamental pulses, will produce amplitude-squeezed light at 1064 nm, further used as the Raman probe.…”
Section: Concept and Methodologymentioning
confidence: 99%
“…Frequency-doubled picosecond pulses will then pump two travelingwave optical parametric amplifiers (OPAs), one of them generating the Raman pump for the SRS. This way, the system will be made synchronization-free and simpler than typical Raman setups [15]. The other OPA, seeded by the fundamental pulses, will produce amplitude-squeezed light at 1064 nm, further used as the Raman probe.…”
Section: Concept and Methodologymentioning
confidence: 99%
“…Yang et al demonstrated 2P NIR-II imaging by using a multicolour ultrafast OPO source (Yang et al, 2013), where brain tissues of a tdTomato-expressing mouse were imaged with 2PE at 1070 nm (Section 3.2, Table 3). Xu et al have developed a periodically poled lithium niobate OPA system operating at 2-ps pulse duration (Xu et al, 2021). In their work, imaging at a depth of 40 μm was achieved in both label-free coherent anti-Stokes Raman scattering (CARS) and 2PE based imaging of mitochondrial flavin adenine dinucleotide autofluorescence in tissue samples.…”
Section: Nir-ii Opo/opa Systemsmentioning
confidence: 99%